Ответ:
[tex]1) \frac{2x-6}{4} =\frac{8-7x}{-7} \\ (2x-6)*(-7)=4*(8-7x)\\-14x+42=32-28x\\14x=10\\x=\frac{10}{14} \\x=\frac{5}{7} \\2) \frac{9}{6x-5} =\frac{3x+5}{2x}\\ 9*2x=(6x-5)*(3x+5)\\18x=18x+30x-15x-25\\15x=25\\x=\frac{25}{15} \\x=\frac{5}{3}[/tex]
Пошаговое объяснение:
да
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex]1) \frac{2x-6}{4} =\frac{8-7x}{-7} \\ (2x-6)*(-7)=4*(8-7x)\\-14x+42=32-28x\\14x=10\\x=\frac{10}{14} \\x=\frac{5}{7} \\2) \frac{9}{6x-5} =\frac{3x+5}{2x}\\ 9*2x=(6x-5)*(3x+5)\\18x=18x+30x-15x-25\\15x=25\\x=\frac{25}{15} \\x=\frac{5}{3}[/tex]
Пошаговое объяснение:
да